2008
DOI: 10.1111/j.1742-7843.2008.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cacao Liquor Polyphenols on Cardiovascular and Autonomic Nervous Functions in Hypercholesterolaemic Rabbits

Abstract: Many epidemiological studies have shown that polyphenols can reduce the risk of mortality from cardiovascular diseases. This study tested the hypothesis that cacao liquor polyphenols have the properties to restore the cardiovascular and autonomic nervous function in an animal model of familial hypercholesterolaemia. Male Kurosawa and Kusanagihypercholesterolaemic rabbits were housed in individual cages in a room where a 12-hr light:dark cycle (lights-on at 8:00 and lights-off at 20:00) was maintained. At 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Heart rate was not increased with HFDC even though it had similar methylxanthine content, indicating that flavanols modulate sympathetic activation. In agreement with this, treatment for six months with a diet enriched in cocoa flavanols resulted in ≈25% lower heart rate in a strain of rabbits, which are genetically prone to hypercholesterolaemia, compared to age-matched control rabbits of the same strain [31]. This difference in heart rate was attributed to cocoa flavanols preventing the decline in parasympathetic function observed in control hypercholesterolaemic animals [31].…”
Section: Effects Of Flavanols On Blood Pressure and Heart Ratesupporting
confidence: 64%
“…Heart rate was not increased with HFDC even though it had similar methylxanthine content, indicating that flavanols modulate sympathetic activation. In agreement with this, treatment for six months with a diet enriched in cocoa flavanols resulted in ≈25% lower heart rate in a strain of rabbits, which are genetically prone to hypercholesterolaemia, compared to age-matched control rabbits of the same strain [31]. This difference in heart rate was attributed to cocoa flavanols preventing the decline in parasympathetic function observed in control hypercholesterolaemic animals [31].…”
Section: Effects Of Flavanols On Blood Pressure and Heart Ratesupporting
confidence: 64%
“…Akita et al [68] studied the effect of dietary intake of cocoa polyphenols on heart rate, blood pressure, and plasma lipid concentrations. The area of atherosclerotic lesions in the aortas of the polyphenol-treated group was significantly smaller than in the control group.…”
Section: Phenolics From Cocoa In Cardiovascular Diseasesmentioning
confidence: 99%
“…Additionally, baroreflex regulation improved. These authors also observed that parasympathetic modulation was preserved in the group that consumed cocoa liquor, differently from the control group, which experienced lower cardiac parasympathetic 22 modulation.…”
Section: Introductionmentioning
confidence: 56%